Copper(II) Sulfate as a New Indicator Substitute to Phenolphthalein in Neutralization Titrimetry - Mir, S.A.; Shakoor, A. (Asian Journal of Chemistry, 2010)
Copper(II) sulfate pentahydrate has been standardized as an advantageous indicator substitute to phenolphthalein in neutralization titrimetry. Copper sulfate 1000 μg mL-1 titrand (ca. 2x 10-3 M near equivalence point) and pheolophthalein 10 μg mL-1 titrand were compared as indicators for standardization of alkali hydroxides and mineral acids' over the normality range 0.03 N to 1 N. The end-point with copper sulfate was shatp, and marked by appearance of a bluish-white turbidity, due to formation of cupric hydroxide near equivalence point, that did not disappear on shaking and standing. The mean normality values obtained with compared indicators did not differ significantly (p> 0.1). Copper sulfate offers certain advantages over phenolphthalein: it is water-soluble, the end-point is highly stable, and it may be used to measure titratable acidity of coloured solutions.